Enhanced performance of GaAs-based betavoltaic batteries by using AlGaAs hole/electron transport layers. (28th July 2022) - Zheng, Renzhou; Lu, Jingbin; Wang, Yu; Liang, Lei; Zeng, Yugang; Qin, Li; Chen, Yongyi; Zhang, Xue; Chen, Ziyi; Li, Xiaoyi; Yuan, Xinxu; Liu, Yumin
Abstract: The GaAs-based betavoltaic batteries with 63 Ni source were demonstrated, in which the AlGaAs hole/electron transport layers were introduced to enhance the transport and collection of radiation-induced carriers. The Monte Carlo codes and COMSOL Multiphysics were combined to predict the output performance of batteries and optimize the structure parameters of energy converter. And the optimized GaAs-based battery with a 6 mCi cm −2 63 Ni source was expected to achieve a short-circuit current density ( J sc ) of 85.6 nA cm −2, an open-circuit voltage ( V oc ) of 0.67 V and a maximum output power density ( P m ) of 43.3 nW cm −2 . Then the GaAs/AlGaAs films were grown by metal organic chemical vapor deposition, and the comb-like electrodes were designed to reduce the absorption loss of beta particles in the p-plane electrode. The photoluminescence and x-ray diffraction were carried out to characterize the growth quality of epitaxial materials. The experimental results showed that the largest J sc of 9.3 nA cm −2, V oc of 55 mV and P m of 143.9 pW cm −2 can be achieved on the 2-busbar electrode battery. And the temperature dependence tests showed that when the temperature decreased to 233.15 K, the V oc and P m increased to 208 mV and 570.5 pW cm −2, respectively. Further improvements in fabrication process are needed to reduce the gap between experiment and prediction. In addition, the optimized structure of energy converter suggests the directions for enhancing the performance of betavoltaic batteries.